Deconstruction of Agency Theory with “Bisa Rumangsa” Culture - Lestari, Wiwik (Fakultas Ekonomi Universitas Samudra, 2023)
The study aims to build a new discourse on agency theory with the application of a “bisa rumangsa” culture in the implementation of corporate governance in order to achieve good corporate governance. Good corporate governance in Indonesia is hampered due to conflict of interests between managers and owners. Each of these managers and owners must understand the limitations of their rights and obligations. Understanding these limits will be born if they apply the culture of “bisa rumangsa”. This research is qualitative research with a radical humanist paradigm. The result of the research is a new concept regarding the application of agency theory by using a “bisa rumangsa” culture.